CFTR and Anoctamin 1 (ANO1) contribute to cAMP amplified exocytosis and insulin secretion in human and murine pancreatic beta-cells - Edlund, Anna (BioMed Central, 2014)
BACKGROUND: Mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene lead to the disease cystic fibrosis (CF). Although patients with CF often have disturbances in glucose metabolism including impaired insulin release, no previous studies have tested the hypothesis that CFTR has a biological function in pancreatic beta-cells. METHODS: Experiments were performed on islets and single beta-cells from human donors and NMRI-mice. Detection of CFTR was investigated using PCR and confocal microscopy. Effects on insulin secretion were measured with radioimmunoassay (RIA). The patch-clamp technique was used to measure ion channel currents and calcium-dependent exocytosis (as changes in membrane capacitance) on single cells with high temporal resolution. Analysis of ultrastructure was done on transmission electron microscopy (TEM) images. RESULTS: We detected the presence of CFTR and measured a small CFTR conductance in both human and mouse beta-cells. The augmentation of insulin secretion at 16.7 mM glucose by activation of CFTR by cAMP (forskolin (FSK) or GLP-1) was significantly inhibited when CFTR antagonists (GlyH-101 and/or CFTRinh-172) were added. Likewise, capacitance measurements demonstrated reduced cAMP-dependent exocytosis upon CFTR-inhibition, concomitant with a decreased number of docked insulin granules. Finally, our studies demonstrate that CFTR act upstream of the chloride channel Anoctamin 1 (ANO1; TMEM16A) in the regulation of cAMP- and glucose-stimulated insulin secretion. CONCLUSION: Our work demonstrates a novel function for CFTR as a regulator of pancreatic beta-cell insulin secretion and exocytosis, and put forward a role for CFTR as regulator of ANO1 and downstream priming of insulin granules prior to fusion and release of insulin. The pronounced regulatory effect of CFTR on insulin secretion is consistent with impaired insulin secretion in patients with CF.